High‐fidelity simulation and nursing students’ anxiety and self‐confidence: A systematic review - Labrague, Leodoro J.; McEnroe‐Petitte, Denise M.; Bowling, Ann M.; Nwafor, Chidozie E.; Tsaras, Konstantinos (Nursing forum (Hillsdale), 2019)
Background As a complementary teaching pedagogy, high‐fidelity simulation remains as an effective form of simulation modality. Empirical evidence has additionally shown high‐fidelity simulation (HFS) to be an effective contributor to students’ learning outcomes. Purpose This paper critically appraised existing scientific articles that covered the influence of utilizing HFS on the effects of nursing students’ anxiety and self‐confidence during undergraduate nursing education. Methods This was a systematic review of scientific articles conducted from 2007 to 2017 on the topic of the influence of using HFS on students’ self‐confidence and anxiety. The literature of six electronic databases (Proquest, SCOPUS, MEDLINE, PubMed Central, CINAHL, and PsychINFO) was reviewed. Results Following the literature search, 35 articles were selected. This review provides updated evidence on the efficacy of HFS in reducing anxiety and enhancing self‐confidence among nursing students when performing nursing duties or managing patients. Moreover, this review highlights the need for more research that examines the impact of HFS on students’ anxiety. Conclusion As this form of simulation is found to be effective in the enhancement of nursing student self‐confidence and the reduction of their anxiety when caring for patients and/or employing nursing skills, the inclusion of simulation‐based activities in all clinical nursing courses is vital.